Making the decision to extend probation supervision at a local agency - Medina, Justin C. (Crime & delinquency, 2017)
The response to a probation violation is often a shared decision between the probation officer and the supervising judge. The result of this decision is a range of possible outcomes. One violation outcome examined here was extended supervision lengths in lieu of incarceration. This decision has been overlooked by prior research but is important to ensure equitable treatment of probationers. This study examined behavioral and organizational factors that resulted in extended supervisions for 6,034 probationers within a large county agency. On average, supervision extensions for these probationers lasted approximately 2 months (62.08 days). The decision-making framework partially explains these extensions because officers had access to poor client behavior indicators. The practical and policy implications of these findings are discussed.